On Some Inequalities Involving Three or More Means - Mustapha Raïssouli; Mohamed Chergui (Abstract and Applied Analysis)
We investigate some results about mean-inequalities involving a large number of bivariate means. As application, we derive a lot of inequalities between four or more means among the standard means known in the literature.